2008
DOI: 10.1007/s10067-008-1013-y
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of differential proteome of human synovial fibroblasts obtained from arthritis

Abstract: There is mounting evidence indicating that the synovial fibroblasts (SFs) contribute to the pathogenesis of rheumatoid arthritis (RA). The present study showed the differential proteins expression pattern of SFs from patients with RA or osteoarthritis (OA) and healthy control. Cellular proteins of cultured SFs were subjected to 2-DE and visualized by silver nitrate staining. A total of 49 spots that were statistically and differentially overexpressed in RA or OA in comparison to healthy ones were identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Enhanced chemiluminescence assay (ECL) (Thermo Scientific, Pierce, USA) was used to develop the membrane and autoradiographed on high performance chemiluminescence film (GE Healthcare) according to the manufactures guidelines. After each step the membrane was washed with 1X PBS [19].…”
Section: Methodsmentioning
confidence: 99%
“…Enhanced chemiluminescence assay (ECL) (Thermo Scientific, Pierce, USA) was used to develop the membrane and autoradiographed on high performance chemiluminescence film (GE Healthcare) according to the manufactures guidelines. After each step the membrane was washed with 1X PBS [19].…”
Section: Methodsmentioning
confidence: 99%
“…Proteomics has been used to study soluble extracts of cartilage [24,63], chondrocyte whole cell lysates [64], synovial fluid [65] and synovial fibroblasts [66], from both normal and OA patients. More recently proteomics has been used to characterise the extracellular space in tracheal in the human aorta [67].…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al (10) compared the expression profiles in synovial membrane samples from patients with RA, patients with osteoarthritis (OA), and patients with ankylosing spondylitis. Bo et al (11) successfully identified 25 differentially overexpressed “spots” in patients with RA or OA compared with healthy subjects.…”
mentioning
confidence: 99%